A case of hepatic intraductal papillary neoplasm of the bile duct - Beltaifa, Dorsaf; Slama, Sana Ben; Guebsi, Sofiene; Atallah, Aziz; Arfa, Nafaa; Lahmar, Ahlem; Bacha, Dhouha (Archives of Case Reports, 2023)
Introduction: Intraductal Papillary Neoplasm of the Bile ducts (IPNB) is a rare entity characterized by exophytic growth of the bile ducts. Case presentation: In this report, we present a 57-year-old male with no prior medical history consulted for upper right abdominal pain, jaundice and pruritus. Abdominal Ultrasound (US) and magnetic resonance imaging/Bili-magnetic resonance were performed. They revealed that the circumferential parietal thickening of the common hepatic duct had extended approximately 4 cm with moderate dilatation of the left intrahepatic bile ducts. Computed tomography showed no evidence of distant metastasis. Biopsy revealed a high-grade intraductal papillary neoplasm. After 40 days, the patient had left hepatectomy with resection of the main bile duct and the gallbladder. Macroscopic examination of the surgical specimen showed a dilatation duct at the hilum with thickening of their walls. The histopathology report revealed multiple intra-hepatic papillary neoplasms with high-grade dysplasia with an invasive carcinoma component in the left hepatic duct without extending to the biliary wall, classified as pT1N0. Conclusion: This premalignant lesion has the potential to transform into invasive carcinoma if not properly diagnosed. Our case illustrates how early identification can lead to potential surgical resection.